Control of Nonlinearly Coupled Oscillators Using a Method of Averaging. Issue 1 (21st October 2015) - Kreuzer, Edwin; Radisch, Christian
Abstract: Container cranes belong to the class of underactuated systems for which the design of control laws is a challenging task. We study the stabilization of certain modes of a crane system using a method of averaging. Based on the local approximation to the system dynamics by a second order Taylor series expansion, the effects of nonlinear couplings are exploited to steer degrees of freedom, for which no linear actuation is available. Rotations of the load about the vertical axis are analyzed and a control method is derived and tested experimentally. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)